Novel fungal metabolites as dual cholinesterase inhibitors: A computational approach for Alzheimer’s disease therapy - Md. Habib Ullah Masum; Syed Mohammad Lokman; Rehana Parvin; Md Shahidur Rahman; Erfanul Haq Chowdhury; Kazi Chamonara; Salma Chowdhury; Ahmad Abdullah Mahdeen; Mst. Mitu Khatun (PLoS ONE, 2025)
Alzheimer’s disease (AD), a progressive neurodegenerative disorder, is a major global health concern, affecting millions worldwide, with its prevalence expected to triple by 2050. Despite the widespread use of traditional drugs like cholinesterase inhibitors and NMDA receptor antagonists, their limited effectiveness requires innovative therapeutic approaches. This work used Computer-Aided Drug Design (CADD) to renovate AD therapies aimed at both acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) using fungal secondary metabolites. Subsequent pharmacokinetic profiles indicated that all metabolites had significant gastrointestinal absorption, blood-brain barrier permeability, and adherence to Lipinski’s Rule of Five, suggesting favourable drug-like properties. Furthermore, these metabolites exhibited little toxicity, except for Lovastatin, which indicated possible carcinogenicity. Molecular docking revealed three main candidates—Fumitremorgin C, Hericenone J, and Lovastatin—with notable binding affinities for AChE and BuChE. Consequently, the Fumitremorgin C showed the highest affinity for AChE (−10.0 kcal/mol), but Hericenone J showed enhanced inhibition of BuChE (−9.2 kcal/mol), suggesting its potential use in advanced stages of AD. Molecular dynamics simulations spanning 100 ns validated the stability of enzyme-ligand complexes, with Hericenone J exhibiting the greatest stability, low RMSD, and strong hydrogen bond interactions. The RMSF analysis further demonstrated that Hericenone J preserved structural integrity, whereas ROG and SASA values validated its compactness and stability. As determined by binding energy calculations, Hericenone J had the most inhibitory potential, followed by Lovastatin. However, Hericenone J’s constant adoption of low-energy conformations, as shown by the principal component and Gibbs free energy analyses, suggested robust and stable interactions with both cholinesterases. With its superior pharmacokinetic profiles, significant binding affinity, and high stability, Hericenone J is the most promising dual cholinesterase inhibitor. These results support the notion that Hericenone J might be an effective treatment for AD if subjected to more preclinical trials.